Sperm nuclear chromatin heterogeneity in infertile subjects - Foresta, C; De Carlo, E; Mioni, R; Zorzi, M (Andrologia, 1989)
Sperm chromatin heterogeneity has been evaluated in infertile males affected by different testicular diseases: 37 subjects had undergone orchidopexy in childhood (ex-cryptorchid), 50 were affected by idiopathic varicocele, 18 had a history of bilateral post-parotitis orchitis and 23 were "idiopathic infertiles". All subjects, except post-parotitis orchitic patients, exhibited significantly higher sperm chromatin heterogeneity than controls, with the highest incidence in ex-cryptorchid and in idiopathic infertiles. Ex-cryptorchid subjects also presented a significant positive linear correlation (p less than 0.001) between degree of sperm chromatin abnormality and percentage of morphological sperm alterations. Four monolateral ex-cryptorchid subjects showed a higher percentage of chromatin heterogeneity even when the cryptorchid testis had been removed during orchidopexy. In patients affected by varicocele, we also observed a significant correlation between chronological age and percentage of chromatin alterations. The results are discussed in relation to the pathogenesis of the disease concerned. Since sperm chromatin heterogeneity appears to be strongly involved in the development of infertility, we would suggest that it should be evaluated in routine diagnostic procedures of male infertility.